IMPERIAL MOSCOW FOUNDING HOSPITAL AT THE TIME OF PATRIOTIC WAR OF 1812 - V.Yu. Al'bitskiy; S.A. Sher ("Paediatrician" Publishers LLC, 2010)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):190-193)